PENGARUH VIRAL MARKETING DAN ELECTRONIC WORD OF MOUTH TERHADAP BRAND TRUST DAN KEPUTUSAN PEMBELIAN PADA PRODUK SCARLETT DI KOTA PEKANBARU - Zam Zam Rahmi; Restuti Sri; Nursanti Aida (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2022)
This research is conducted to determine the effect of Viral Marketing andElectronic Word of Mouth on Brand Trust and Purchase Decisions on ScarlettProducts in Pekanbaru City. In this study there are four variables, namely ViralMarketing (X1), Electronc Word of Mouth (X2), Brand Trust (Y1) and PurchaseDecision (Y2). The population in this study were all users of Scarlett products witha sample of 126 respondents who were selected using the purposive samplingmethod with the criteria that users of Scarlett products in Pekanbaru city andaged over 17 years. Collecting data in this study is by giving a questionnaire tothe respondents. Meanwhile, in terms of data analysis, this study uses pathanalysis method with the help of SPSS version 26. The results of this studyindicate that: 1) Viral Marketing has positive and significant effect on BrandTrust, 2) Electronic Word of Mouth has a positive and significant effect on BrandTrust, 3) Viral Marketing has positive and significant effect on PurchaseDecisions, 4) Electronic Word of Mouth has positive and significant effect onPurchase Decisions, 5) Brand Trust has positive and significant effect onPurchase Decisions, 6) Viral Marketing has positive and significant effect onPurchase Decisions through Brand Trust, 7) Electronic Word of Mouth onpositive and significant Purchase Decisions through Brand Trust. Keywords: Viral Marketing, Electronic Word of Mouth, Brand Trust andPurchase Decision